Skilled interviewing - Keats, Daphne M. (Hawthorn, Vic. : Australian Council for Educational Research, 1993)
Psychological bases of interviewing. Types of interview. Structuring the interview. Techniques of interviewing. Non-verbal communication. Some difficult cases...
Keywords: Interviewing; Interviewing